A multicenter clinical epidemiology of pediatric pneumococcal meningitis in China: results from the Chinese Pediatric Bacterial Meningitis Surveillance (CPBMS) 2019–2020 - Wang, Caiyun; Xu, Hongmei; Liu, Gang; Liu, Jing; Yu, Hui; Chen, Biquan; Zheng, Guo; Shu, Min; Du, Lijun; Xu, Zhiwei; Huang, Lisu; Li, Haibo; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Abstract Objective: To analyze the clinical epidemiological characteristics of pneumococcal meningitis (PM), and drug sensitivity of S. pneumoniae isolates in children. Methods: A retrospective analysis was performed on the clinical, laboratory microbiological data of 160 hospitalized children less than 15 years of age with PM. Results: A total of 160 PM patients were diagnosed. The onset age was 15 days to 15 years old, and the median age was 1 year and 3 months. There were 137 cases (85.6%) in the 3 months to <5 years age group, especially in the 3 months to <3 years age group (109 cases, 68.2%); S. pneumoniae was isolated from cerebrospinal fluid (CSF) culture in 95(35.6%), and 57(35.6%) in blood culture. The positive rates of S. pneumoniae detection by CSF metagenomic next-generation sequencing (mNGS)and antigen detection method were 40.2% (35/87) and 26.9% (21/78). Fifty-five cases (34.4%) had one or more predisposing factors of bacterial meningitis; and 113 cases (70.6%) had one or more extracranial infection diseases Fever (147, 91.9%) was the most common clinical symptom, followed by vomiting (61, 38.1%) and altered mental status (47,29.4%). Among 160 children with PM, the main intracranial imaging complications were subdural effusion and (or) empyema in 43 cases (26.9%), hydrocephalus in 24 cases (15.0%), cerebral abscess in 23 cases (14.4%), intracranial hemorrhage in 8 cases (5.0%), and other cerebrovascular diseases in 13 cases (8.1%) including encephalomalacia, cerebral infarction, and encephalatrophy. Subdural effusion and (or) empyema and hydrocephalus mainly occurred in children < 1 years old (90.7% (39/43) and 83.3% (20/24), respectively). 17 cases with PM (39.5%) had more than one intracranial imaging abnormality. The cure and improvement rate were 22.5%（36/160）and 66.3%（106/160）, respectively. 18 cases (11.3%) had an adverse outcome, including 6 cases withdrawing treatment therapy, 5 cases unhealed, 5 cases died, and 2 recurrences. Conclusions： Pediatric PM is more common in children aged 3 months to < 3 years old. Intracranial complications mostly occur in children < 1 year of age with fever being the most common clinical manifestations and subdural effusion and (or) empyema and hydrocephalus being the most common complications, respectively.